Epidemiology of the 2020 pandemic of COVID‐19 in the state of Georgia: Inadequate critical care resources and impact after 7 weeks of community spread - Justin Xavier Moore; Marvin E. Langston; Varghese George; Steven S. Coughlin (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Novel coronavirus (COVID‐19) is a global pandemic currently spreading rapidly across the United States. We provide a comprehensive look at COVID‐19 epidemiology across the state of Georgia, which includes vast rural communities that may be disproportionately impacted by the spread of this infectious disease. Methods All 159 Georgia counties were included in this study. We examined the geographic variation of COVID‐19 in Georgia from March 3 through April 24, 2020 by extracting data on incidence and mortality from various national and state datasets. We contrasted county‐level mortality rates per 100,000 population (MRs) by county‐level factors. Results Metropolitan Atlanta had the overall highest number of confirmed cases; however, the southwestern rural parts of Georgia, surrounding the city of Albany, had the highest bi‐weekly increases in incidence rate. Among counties with >10 cases, MRs were highest in the rural counties of Randolph (233.2), Terrell (182.5), Early (136.3), and Dougherty (114.2). Counties with the highest MRs (22.5–2332 per 100,000) had a higher proportion of: non‐Hispanic Blacks residents, adults aged 60+, adults earning <$20,000 annually, and residents living in rural communities when compared with counties with lower MRs. These counties also had a lower proportion of the population with a college education, lower number of ICU beds per 100,000 population, and lower number of primary care physicians per 10,000 population. Conclusions While urban centers in Georgia account for the bulk of COVID‐19 cases, high mortality rates and low critical care capacity in rural Georgia are also of critical concern.